Uji Fisika Pada Sabun Mandi Padat Buah Naga Merah (Hylocereus polyrhizus) Asal Kabupaten Sidrap - Syahrul Mubarak; Dewi Lidiawati; Nurul Khaerani (Journal of Pharmaceutical and Health Research, 2022)
The research carried out is a physical test study on red dragon fruit (Hycolereus Polyrhizus) solid bath soap, which is to find out the soap that has been treated is safe when used on the body. The results of the research that have obtained the pH test of solid bath soap sample 10% = 6.4, sample 15% = 6.2, sample 20% = 6.6 which is acidic indicates that it does not meet the standards that have been set (SNI, 1994). The height test of solid soap foam is 10% = 15 cm, 15% = 18 cm, 20% = 16 cm. And the water content test is sample 15% = 58.17g, sample 10% = 50.10g, sample 20% = 59.54g